2022
DOI: 10.3389/fnmol.2022.872471
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Pyroptosis in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a disease characterized by insidious and progressive neurodegeneration, with clinical syndromes of memory and visuospatial skills damage. The pathogenic mechanism of AD is complex in which neural inflammation and neuron death play important roles. Pyroptosis, an inflammatory programmed cell death, has been reported to be involved in neuron death. Pyroptosis is executed by the protein family of gasdermins which punch pores on plasma membrane when activated by the upstream signals inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Further probing of pathways significantly altered by amyloid-positivity was conducted using the Reactome database ( Figure 6B ), which revealed pathways related to “DNA methylation” and “chromatin organization”. Additionally, a “defective pyroptosis” pathway was identified, possibly indicating processes linked to increased cell death (71). We probed this further using Gene Ontology enrichment analysis on the plasma proteins associated with amyloid-positivity and found consensus with altered biological processes related to chromatin organization and assembly ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further probing of pathways significantly altered by amyloid-positivity was conducted using the Reactome database ( Figure 6B ), which revealed pathways related to “DNA methylation” and “chromatin organization”. Additionally, a “defective pyroptosis” pathway was identified, possibly indicating processes linked to increased cell death (71). We probed this further using Gene Ontology enrichment analysis on the plasma proteins associated with amyloid-positivity and found consensus with altered biological processes related to chromatin organization and assembly ( Figure 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…Plasma levels of SAA1 were found to be upregulated in amyloid-positive subjects, which was supported by pathway analysis and enrichment of gene ontology terms linked to inflammation. Pathway analysis on plasma proteins altered in amyloid-positive subjects highlighted changes in processes previously linked to AD pathogenesis, including the blood-brain barrier (85, 86), programmed cell death by pyroptosis (71), and altered epigenetic mechanisms related to DNA and chromatin manipulations (87). A study measuring plasma proteins in AD cases and controls highlighted some of these pathways (“regulation of apoptotic process” and “extracellular matrix organization”) but also distinct pathways (29), possibly due to the more advanced ages and/or pathology in their cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that pyroptosis is closely related to the pathogenesis of AD [19], and recently, Cell reported [12] that inhibiting the pyroptosis pathway may constitute a breakthrough in the molecular mechanism of AD treatment. Moreover, the expression level of Caspase-1 in the brains of APP/PS1 transgenic mice increased.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis can cause inflammation that is activated by extracellular or intracellular stimuli [ 52 ] and is associated with various diseases, such as cardiovascular disease [ 53 ], Alzheimer’s disease [ 54 ], atherosclerosis [ 55 ], and muscle atrophy [ 56 ]. A recent study showed that pyroptosis occurs during dexamethasone-induced muscle atrophy [ 57 ].…”
Section: Discussionmentioning
confidence: 99%